Fabrication of centrifugally spun prepared poly(lactic acid)/gelatin/ciprofloxacin nanofibers for antimicrobial wound dressing. Issue 61 (31st October 2019) - Xia, Lei; Lu, Linlin; Liang, Yuxia; Cheng, Bowen
Abstract : Centrifugal spinning is a novel technology for producing ultrafine fibers in high yield with diameters ranging from micro to nanometers. Abstract : Centrifugal spinning is a novel technology for producing ultrafine fibers in high yield with diameters ranging from micro to nanometers. The obtained fibers have potential applications in the field of tissue engineering, wound dressing, and biomedicine etc. In this paper, a system of poly(lactic acid)/gelatin (PLA/GE) nanofibers loaded with ciprofloxacin (CPF) drug for wound dressings were successfully prepared by centrifugal spinning. The nanofibers were characterized by scanning electron microscopy (SEM) coupled with energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), thermal gravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR). In addition, the nanofibers' properties in terms of hydrophilicity, antibacterial properties and in vitro drug release were further investigated. The results showed that the CPF drug was successfully loaded and in an amorphous state in the PLA/GE nanofibers, the surface of the nanofibers was smooth and the nanofibers' diameter became large after the drug was loaded. The thermal stability of the nanofiber was reduced while the hydrophilicity was improved. Antibacterial and in vitro drug release experiments showed that the nanofibers have obvious antibacterial properties and have the positive effect of sustained release of the drug. Drug-loaded PLA/GE nanofibers could be good candidates for wound dressing.